2023
DOI: 10.1186/s12877-023-04473-1
|View full text |Cite
|
Sign up to set email alerts
|

Psychological resilience and quality of life among middle-aged and older adults hospitalized with chronic diseases: multiple mediating effects through sleep quality and depression

Jiashuang Xu,
Lin Zhang,
Hong Sun
et al.

Abstract: Background The present study is intended to examine the multiple mediating roles of sleep quality and depression in the relationship between psychological resilience and quality of life in middle-aged and older adults hospitalized with chronic diseases. Methods From October 2, 2021, to February 27, 2022, a questionnaire survey was conducted using a multistage stratified sampling method among 339 middle-aged and older adults (45 years and over) hosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…The study included participants who met four requirements: (1) could not have been younger than 45 years old; (2) had no documented history or diagnosis of neurological or psychiatric diseases ( 1 ); (3) could communicate well and had no comprehension difficulties; and (4) volunteered to participate in the study. Exclusion criteria: (i) patients with serious psychiatric disorders who are unable to communicate and express themselves normally; (ii) patients who did not cooperate with this investigation ( 3 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The study included participants who met four requirements: (1) could not have been younger than 45 years old; (2) had no documented history or diagnosis of neurological or psychiatric diseases ( 1 ); (3) could communicate well and had no comprehension difficulties; and (4) volunteered to participate in the study. Exclusion criteria: (i) patients with serious psychiatric disorders who are unable to communicate and express themselves normally; (ii) patients who did not cooperate with this investigation ( 3 ).…”
Section: Methodsmentioning
confidence: 99%
“…Chronic non-communicable diseases (often referred to as chronic diseases) are an abbreviation for a group of diseases that are not contagious but have an insidious onset, a long treatment period, and incurable ( 1 ). In the modern world, chronic diseases are a significant hazard to human health, accounting for almost 36 million deaths annually worldwide ( 2 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, some studies have suggested that the more positive the coping, the better the outcome, a coping strategy is not always effective, coping is context-speci c and the coping effect changes dynamically, excessive confrontation with the disease can cause anxiety, leading to excessive attention to the disease and its side effects, resulting in patients with symptomatic embarrassment [30][31][32] , and appropriate avoidance of certain patients may be better for them. Therefore, ophthalmologists should carry out a reasonable assessment and appropriate interventions for patients with DED, such as self-expression interventions, i.e., patients express their inner feelings and thoughts through verbal and written forms, to improve the patient's psychological resilience and to promote their positive coping with the disease, and the higher the level of psychological resilience of the patients, the more conducive they are to coping with the disease with a positive attitude [33] . It has been proved that improving patients' symptom perception and coping ability can reduce the adverse consequences of uncomfortable symptoms and improve their negative emotions.…”
Section: Actively Channeling Negative Disease Perceptions and Negativ...mentioning
confidence: 99%